Homofiles : Theory, Sexuality, and Graduate Studies. - Battis, Jes, 1979- (Lexington Books, 2011)
Homofiles: Theory, Sexuality, and Graduate Studies, edited by Jes Battis, collects the work of gay, lesbian, and transgender graduate students who are pursuing studies across the humanities. The contributors' essays address the various relationshipsbetween sexuality and scholarship within their respective programs, and present arguments on topics ranging from queer literature to police brutality. This is the first anthology to specifically explore the role of queer and transgender intellectuals-in-training within the academy, and the contributors both analyze and challenge the structures of academia that they are working in as cultural critics.